Real-time 3D single molecule tracking - Shangguo Hou (Nature Portfolio, 2020)
Single molecule observation has been limited to tethered molecules to ensure that the target remains in the field of view (FOV). Here, the authors develop a real-time tracking method that locks onto rapidly diffusing targets and tracks them in a 3D volume, enabling single molecules to remain in the FOV for minutes at a time.